2019
DOI: 10.1038/s41467-019-12923-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of ZCCHC4 in m6A-methylation of 28S rRNA

Abstract: N6-methyladenosine (m6A) modification provides an important epitranscriptomic mechanism that critically regulates RNA metabolism and function. However, how m6A writers attain substrate specificities remains unclear. We report the 3.1 Å-resolution crystal structure of human CCHC zinc finger-containing protein ZCCHC4, a 28S rRNA-specific m6A methyltransferase, bound to S-adenosyl-L-homocysteine. The methyltransferase (MTase) domain of ZCCHC4 is packed against N-terminal GRF-type and C2H2 zinc finger domains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 35 publications
2
79
0
Order By: Relevance
“…In patients with HCC, the expression of ZCCHC4 and m 6 A on 28S rRNA in cancer tissues was significantly increased as compared to that in the surrounding healthy tissues, whereas ZCCHC4 knockout in a xenograft mouse model eliminates m 6 A modification on 28S rRNA and then decreases global translation activity, which contributes to the inhibition of HCC cell proliferation and reduction in liver tumor size; thus, highlighting the essential role of m 6 A rRNA modification in mRNA translation and tumor progression [26]. Consistent with this finding, van Tran et al confirmed ZCCHC4 as a 28S rRNA m 6 A4220 methyltransferase that acts only on rRNAs [82], and further studies on the structure and regulation of ZCCHC4 in m 6 A methylation of 28S rRNA showed that the specific binding and methylation of ZCCHC4 to substrates depended on the stem loop structure of 28S rRNA [83]. In addition, the findings that ZCCHC4 is located in nucleoli, where the ribosomes are assembled, and ZCCHC4 interacts with proteins involved in RNA metabolism provide a possible mechanism by which ZCCHC4 influences RNA translation by regulating ribosomal assembly and biogenesis [84].…”
Section: Ribosomal Rnasmentioning
confidence: 77%
“…In patients with HCC, the expression of ZCCHC4 and m 6 A on 28S rRNA in cancer tissues was significantly increased as compared to that in the surrounding healthy tissues, whereas ZCCHC4 knockout in a xenograft mouse model eliminates m 6 A modification on 28S rRNA and then decreases global translation activity, which contributes to the inhibition of HCC cell proliferation and reduction in liver tumor size; thus, highlighting the essential role of m 6 A rRNA modification in mRNA translation and tumor progression [26]. Consistent with this finding, van Tran et al confirmed ZCCHC4 as a 28S rRNA m 6 A4220 methyltransferase that acts only on rRNAs [82], and further studies on the structure and regulation of ZCCHC4 in m 6 A methylation of 28S rRNA showed that the specific binding and methylation of ZCCHC4 to substrates depended on the stem loop structure of 28S rRNA [83]. In addition, the findings that ZCCHC4 is located in nucleoli, where the ribosomes are assembled, and ZCCHC4 interacts with proteins involved in RNA metabolism provide a possible mechanism by which ZCCHC4 influences RNA translation by regulating ribosomal assembly and biogenesis [84].…”
Section: Ribosomal Rnasmentioning
confidence: 77%
“…In addition to the MTC, other m 6 A writers have also been identified in recent years, including METTL16, METTL5, and ZCCHC4 ( Fig. 1a and Table 1), which are responsible for the deposition of m 6 A into structured RNAs, such as U6 snRNA, 28S rRNA, and 18S rRNA, and in some cases, the introns of mRNA [15][16][17][18][19][20][21][22]. The MTC core component METTL3-METTL14 heterodimer catalyzes most of m 6 A methylations in mRNA, with METTL3 being the only catalytic subunit that uses Sadenosylmethionine (SAM) as the methyl donor [52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…International Publisher demethylases (FTO and ALKBH5) [29,30], and recognized by RNA binding proteins, including YTHDF1/2/3, YTHDC1/2, IGF2BP1/2/3, hnRNPs [14,16,[31][32][33][34][35][36][37][38][39]. m 6 A modification of U6 snRNA and structural RNA, 18 S rRNA and 28 S rRNA, the 5'cap m 6 A m , and U2 snRNA internal m 6 A m are methylated by METTL16 [10,11,40], METTL5 [41], ZCCHC4 [9,42] and PCIF1 [43,44], respectively. Recently, METTL4 was shown to be a U2 snRNA internal m 6 A m methyltransferase [45].…”
Section: Ivyspringmentioning
confidence: 99%